Research on the Influence of Shadow Education on the Performance of Different Subjects in Junior High School: Empirical Analysis based on CEPS ( 2013-2014 ) - Xu, Shuya (International Journal of Social Sciences and Public Administration, 2024)
The purpose of this study is to describe and evaluate the contribution of shadow education to students ’ academic performance through the survey data of the student baseline of the China Education Panel Survey (CEPS), and to understand its impact on the academic performance of different disciplines. Based on the results of data analysis, it provides policy recommendations and practical guidance for the government, schools and families on how to make more effective use of shadow education resources and how to improve and optimize the educational environment. The results show that mathematics and English extracurricular tutoring significantly improve mathematics and English scores, while Chinese is not. The appropriate amount of tutoring on holidays and weekends is positively correlated with performance, but too long tutoring from Monday to Friday leads to a decline in performance, and the length of tutoring is not as long as it is, and the moderation is the best.